Blood pressure and heart failure: focused on treatment - Kyeong-Hyeon Chun; Seok-Min Kang (BMC, 2024)
Abstract Heart failure (HF) remains a significant global health burden, and hypertension is known to be the primary contributor to its development. Although aggressive hypertension treatment can prevent heart changes in at-risk patients, determining the optimal blood pressure (BP) targets in cases diagnosed with HF is challenging owing to insufficient evidence. Notably, hypertension is more strongly associated with HF with preserved ejection fraction than with HF with reduced ejection fraction. Patients with acute hypertensive HF exhibit sudden symptoms of acute HF, especially those manifested with severely high BP; however, no specific vasodilator therapy has proven beneficial for this type of acute HF. Since the majority of medications used to treat HF contribute to lowering BP, and BP remains one of the most important hemodynamic markers, targeted BP management is very concerned in treatment strategies. However, no concrete guidelines exist, prompting a trend towards optimizing therapies to within tolerable ranges, rather than setting explicit BP goals. This review discusses the connection between BP and HF, explores its pathophysiology through clinical studies, and addresses its clinical significance and treatment targets.